Simple identification of Trichophyton tonsurans by chlamydospore‐like structures produced in culture media. Issue 12 (4th December 2013) - Mochizuki, Takashi; Anzawa, Kazushi; Sakata, Yuichi; Fujihiro, Machiko
Abstract Trichophyton tonsurans is known to be the causative agent of a worldwide epidemic of dermatophytoses among contact sports practitioners, and is spreading among the general population of Japan. Prompt and simple identification of T. tonsurans in diagnostic laboratories is crucial to control infection. The present study evaluated the availability of observation of chlamydospore‐like structures grown in culture media as a characteristic for identification of T. tonsurans. Twenty‐five strains of T. tonsurans and five strains each of Trichophyton verrucosum, Trichophyton rubrum and Trichophyton mentagrophytes were inoculated on Mycosel agar plates and inoculated Petri dishes were observed by light microscopy from the reverse side. Twenty‐three of 25 T. tonsurans strains showed chlamydospore‐like structures within 5 days, and all strains at day 8. The numbers of chlamydospore‐like structures were very abundant in most strains. The majority of strains of other species showed no chlamydospore‐like structures, or very few when present. Positive for chlamydospore‐like structures among 15 strains other than T. tonsurans was one strain at day 5 and six strains at day 8. As for the identification of T. tonsurans, presence of chlamydospore‐like structures showed 92.0% sensitivity (23/25) and 93.3% specificity (14/15) at day 5, and 100% sensitivity (25/25) and 60.0% specificity (9/15) at day 8. Electron microscopic findings suggest chlamydospore‐like structures are not true chlamydospores but are produced by inflation of actively growing hyphae by developing vacuoles in cells. In conclusion, observation of development of chlamydospore‐like structures in culture media is the simplest method for identification of T. tonsurans.